Sustainable design from theorizing to application - Mohammed Ali Ali (Iraqi Journal of Architecture and Planning, 2018)
The architecture field is considered as one of the most prominent specialized fields which the sustainability can be seen in the theoretical and applied level that is committed to the sustainability and its concepts, taking in consternation the complicity that characterize this field came the variety in the act of sustainability. However, this commitment and variety have not been framed (here lies the research problem), the Aim of the research is find a clear framework for the application of sustainability in architecture.To that the research was focused in searching for the way that make the sustainable design be seen in architecture, and the possibility that can be achieved on the other hand by an analytic study in comparison to practical experiments to the sustainable design applications which can be able to make the theoretical framework for the practice of sustainability in architecture as follows: (Future visions and strategies for sustainable cities, Global forums - World Expo, Standards and systems that assess the sustainability of the projects, Assistant computer programs and tools for the sustainable design, Architectural projects.)The analytic and comparison method follow for the international and Arabic practical experiments, to achieve the research goal, which seeks to frame the scientific applications of the sustainable design in architecture.Keywords: Sustainability, Sustainable design, Sustainable architecture. Sustainability practical applications.